A review of the Japanese species of the genus Xanthocampoplex Morley, 1913 (Hymenoptera, Ichneumonidae, Campopleginae), with description of a new genus - Watanabe, Kyohei (Zootaxa, 2019)
Japanese species of the genus Xanthocampoplex Morley, 1913 are reviewed. Three species previously belonging to this genus, X. caloptiliae Kusigemati, 1982, X. kumatai Kusigemati, 1982 and X. spulerinae Kusigemati, 1982 share unique character states and thus I describe a new genus, Kusigematia gen. nov. including K. caloptiliae (Kusigemati, 1982) comb. nov., K. kumatai (Kusigemati, 1982) comb. nov. (type species of the genus) and K. spulerinae (Kusigemati, 1982) comb. nov. This genus morphologically resembles Xanthocampoplex, but it can be distinguished by the following combination of character states: flagellum covered with long setae and with an erect very long seta on apex (these setae short in Xanthocampoplex); all flagellomeres longer than wide (at least some apical flagellomeres as long as wide or wider than long in Xanthocampoplex); tarsal claws small and simple (small to moderate length and pectinate in Xanthocampoplex); apex of dorsal valve of ovipositor with a distinct convexity behind of notch (not convex in Xanthocampoplex), body, excluding legs and wings, largely black to blackish brown (yellow or black with conspicuous large yellow markings in Xanthocampoplex); host is Gracillariidae (Cossidae and Crambidae in Xanthocampoplex). Xanthocampoplex chinensis Gupta, 1973 is newly recorded from Japan and Palaearctic region.